PENGETAHUAN LOKAL DAN PEMANFAATAN TUMBUHAN OLEH MASYARAKAT LOKAL PULAU KABAENA- SULAWESI TENGGARA - Mulyati Rahayu; Rugayah Rugayah (BERITA BIOLOGI, 2010)
An ethnobotanical research focusing on the local people Moronene of the Wumbu Buro village, eastern part of Kabaena island,South East Sulawesi, was carried out using semi structural interviews and field observation. The local people practiced a traditional agricultural system. The results indicated maize Zea mays L., rice Oryza sativa L. and some other vegetable plants becoming the first priority species planted before cultivating horticultural plants such as cashew Anacardium occidentale L., cacao Theobroma cacao L. and coconut Cocos nucifera L. A total of 65 plant species were used by the local people for their daily needs, such as for food, utensil, roof, waving, medicine & cosmetic purposes including a plant species used for harvesting the palm sugar.The indigenous knowledge owned by the local people in utilizing plant species is discussed.